2016
DOI: 10.1136/neurintsurg-2016-012349
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria as an independent risk factor for contrast-induced acute kidney injury and mortality in patients with stroke undergoing cerebral angiography

Abstract: BackgroundThe correlation between proteinuria and contrast-induced acute kidney injury (CI-AKI) in patients with cerebrovascular disease is still unknown.ObjectiveTo determine whether proteinuria is a risk factor for CI-AKI and death in patients with stroke undergoing cerebral angiography.MethodsData from 2015 patients with stroke undergoing cerebral angiography between January 2009 and December 2013 were retrospectively collected. Clinical parameters were obtained from the hospital's computerized database. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…[9][10][11] Previous studies have drawn conflicting conclusions on the risk factors associated with PC-AKI. [12][13][14] Even though there are studies on PC-AKI after either CTA or cerebral angiography, studies that consider concomitant CTA and cerebral angiography performed within a short duration are lacking. 10,11 In addition, there is scant literature on the occurrence of PC-AKI according to the baseline renal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Previous studies have drawn conflicting conclusions on the risk factors associated with PC-AKI. [12][13][14] Even though there are studies on PC-AKI after either CTA or cerebral angiography, studies that consider concomitant CTA and cerebral angiography performed within a short duration are lacking. 10,11 In addition, there is scant literature on the occurrence of PC-AKI according to the baseline renal function.…”
Section: Discussionmentioning
confidence: 99%
“…The task of accurately predicting contrast-induced kidney injury in patients with suspected stroke who require rapid management in the ED could likely delay the decision-making by neurologists and ED physicians. [12][13][14] Therefore, presenting grounds for treatment that can be the criteria for judgment by ED physicians can be very important. Recently, Jia et al 9 reported no significant difference in the incidence of PC-AKI between CTA only and with a combination of CTA and DSA.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, a large cohort study with 920,985 adults reported that the risk of acute kidney injury increased substantially with the presence and severity of proteinuria (20). Subsequent studies implicated proteinuria as a risk factor of AKI after intra-arterial contrast administration in the settings of percutaneous coronary intervention and stroke intervention (2123). Piskinpasa et al reported that PC-AKI was significantly higher when proteinuria exceeded 1 g/day (24).…”
Section: Discussionmentioning
confidence: 99%
“…Proteinuria is often associated with clinical conditions such as stroke and sleep apnea. These conditions are presented with reduced renal perfusion and moderate to severe hypoxia 12,14 . Accumulated evidence suggests that hypoxia contributes to the proteinuria and pathogenesis of chronic kidney disease (CKD) 6,7,10,[15][16][17] .…”
Section: Introductionmentioning
confidence: 99%